1986
DOI: 10.1021/np50048a049
|View full text |Cite
|
Sign up to set email alerts
|

Methyl β-Orcinolcarboxylate and Atranol from the Lichen Stereocaulon vesuvianum

Abstract: Extracts of Stereocaulon vesuvianum Pets, showed strong activity against Bacillus subtilis and Escherichia coli and a distinct activity against Penicillium digitatum and Saccharomyces cerevisiae. By preparative hplc, methyl ß-orcinolcarboxylate (strongly antifungal) and atranol (strongly antibacterial) were isolated, and it was shown that both compounds are present as natural products and are not artifacts formed during workup. Methyl ß-orcinolcarboxylate was recently suggested to be present in S. vesuvianum b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…extracts have been identified previously, including atranol (compound 3), chloroatranol (compound 19), atraric acid (compound 7), everninate (compound 11), haematommate (compound 13), orsellinates (compounds 4, 6, 8) and lecanorin (compound 5). [1][2][3][4] The antimicrobial activity of these compounds against various fungi and Gram-positive and Gram-negative bacteria has also been demonstrated in previous reports. 13,14) However, an examination of the antibacterial activity of these oakmoss components against L. pneumophila and Legionella spp.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…extracts have been identified previously, including atranol (compound 3), chloroatranol (compound 19), atraric acid (compound 7), everninate (compound 11), haematommate (compound 13), orsellinates (compounds 4, 6, 8) and lecanorin (compound 5). [1][2][3][4] The antimicrobial activity of these compounds against various fungi and Gram-positive and Gram-negative bacteria has also been demonstrated in previous reports. 13,14) However, an examination of the antibacterial activity of these oakmoss components against L. pneumophila and Legionella spp.…”
Section: Discussionsupporting
confidence: 53%
“…3,4) However, to date there have been no reports concerning the antibacterial activity of these components against Legionella pneumophila strains. We previously demonstrated that 101 natural and synthetic fragrance ingredients exhibit antimicrobial activity against representative Gram-positive and Gram-negative bacteria, as well as various fungi.…”
mentioning
confidence: 99%
“…In our investigation, two new abietane diterpenoids, called hanagokenols A (1), and B (2), along with 15 known compounds including abietane, [3][4][5] labdane, [6][7][8] isopimarane 9) diterpenoids, monocyclic aromatic compound, 10,11) depside, 12,13) and dibenzofuran 14,15) were isolated from C. rangiferina. We describe here the isolation, purification, and structural elucidation of the unique abietane diterpenes, 1 and 2, primarily by extensive NMR experiments, and the antimicrobial activities of all the isolated compounds against methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococci (VRE).…”
mentioning
confidence: 99%
“…The AcOEt extract was fractionated into seven fractions by column chromatography (silica gel), followed by repeated separations of their seven portions by chromatography over silica gel. Reversed-phase silica gel furnished hanagokenols A (1), and B (2), obtuanhydride (3), 3) sugiol (4), 4) 5,6-dehydrosugiol(5), 4) montbretol (6), 5) cis-communic acid (7), 6) imbricatoloic acid (8), 7) 15-acetylimbricatoloic acid (9), 8) junicedric acid (10), 8) 7a-hydroxysandaracopimaric acid (11), 9) b-resorylic acid (12), 10) atranol (13), 11) barbatic acid (14), 12) homosekikaic acid (15), 13) didymic acid (16), 14) and condidymic acid (17 . These data suggested that 1 was an abietane-type diterpene, as compounds 3-6.…”
mentioning
confidence: 99%
“…Atranorin (2): Colorless needles (CH 2 Cl 2 ) (Brassy et al, 1982). Methyl-b-orcinolcarboxylate (3): Colorless small needles (CH 2 Cl 2 ) (Caccamese et al, 1986). Zeorin (4): Colorless needles (CH 2 Cl 2 ) (Yosioka et al, 1972).…”
Section: Heterodermia Leucomelosmentioning
confidence: 99%